Diets of Steller sea lions off the coast of Hokkaido, Japan: An inter‐decadal and geographic comparison. (22nd December 2017) - Goto, Yoko; Wada, Akihiko; Hoshino, Noboru; Takashima, Takahiro; Mitsuhashi, Masaki; Hattori, Kaoru; Yamamura, Orio
Abstract: Inter‐decadal and geographic variations in the diets of Steller sea lion, Eumetopias jubatus, were examined based on the contents of 408 stomachs collected from coastal areas around Hokkaido Island during the periods 1994–1998 and 2005–2012. The most important prey species in the 1990s were gadid fishes (walleye pollock [ Gadus chalcogrammus ], Pacific cod [ Gadus microcephalus ] and saffron cod [ Eleginus gracilis ]). The frequency of occurrence and gravimetric contribution of gadids decreased in the 2000s latter period at three study sites (Rausu, Shakotan and Rebun) and were replaced by Okhotsk Atka mackerel ( Pleurogrammus azonus ) and smooth lumpsucker ( Aptocyclus ventricosus ). However, analysis based on gravimetric composition indicated that the dietary diversity of prey showed only a slight inter‐decadal difference, reflecting the wide diversity of prey ingested during both study periods. These results indicate that Steller sea lions along the Hokkaido coast are opportunistic feeders that utilize a wide variety of prey, and appear to feed mainly upon prey that is easily obtained.